Bagaimana Hubungan antara Belief in Math dan Metode Project Based Learning dalam Pembelajaran Matematika? - Sumantri, Cahya Mar'a Saliha (Universitas PGRI Semarang, 2024)
Belief in math is a students' attitudes toward mathematics, where students can give a positive or negative response to the mathematics learning activities. Students are given a math problem and when complete it, they will think first, then by the time students are expected to make sure the answer and concepts used are appropriate. Any given cultivated mathematical problems always follow the real-world context in which the students participate actively and creatively. The task of project-based learning that given by the teacher to the students is one of some ways to solve the problem and make the students understand on their own way. This method was literature review that used to find out the relationship between student belief in math and learning mathematics using project based learning method. The relationship between belief in in math and project based learning is in their project learning that consists of several steps on their application aims to help students further develop, not only in knowledge but also belief in math student as the passage of the process of the project, students will be challenge theirself and trust to himself to completing their own projects.